Faktor-faktor yang mempengaruhi masalah ponteng di sekolah menengah daerah Segamat - Abd. Wahab, Nosiah (2014)
The purpose of the study is to determine the type of truancy that occurs most frequently in the School District of Segamat Johor. Studies were also conducted to determine the most dominant factor influencing truancy problems that influence students' attitudes , peers, school , family , school environment , teachers and the environment. The level of discipline and management skills training needs are also examined. Quantitative methods are used and a sample of 240 teachers from nine secondary schools of Segamat District. Data were analyzed using the software Statistical Package for Social Science (SPSS) version 19.0 . The results showed that skipping school activities is most likely to occur than skipping class and truancy The result also shows that, peer is the most dominant factor that drives student to miss school with a high mean value of 3.60 . Other factors that influence are the environment, teachers, students' attitudes, family and school environment . There are significant differences between peer location and environmental factors with the location of the school . The level of discipline management skills among teachers is at a high level and training requirements are moderate. The implication of the study is that all parties should jointly cared of truancy problems and try to find the best solution in order to produce world-class human capital for future generation.